A Cu‐only superoxide dismutase from stripe rust fungi functions as a virulence factor deployed for counter defense against host‐derived oxidative stress. (8th October 2020) - Zheng, Peijing; Chen, Liyang; Zhong, Suye; Wei, Xiaobo; Zhao, Qi; Pan, Qinglin; Kang, Zhensheng; Liu, Jie
Summary: Plants quickly accumulate reactive oxygen species (ROS) to resist against pathogen invasion, while pathogens strive to escape host immune surveillance by degrading ROS. However, the nature of the strategies that fungal pathogens adopt to counteract host‐derived oxidative stress is manifold and requires deep investigation. In this study, a superoxide dismutase (SOD) from Puccinia striiformis f. sp. tritici ( Pst ) PsSOD2 with a signal peptide (SP) and the glycophosphatidyl inositol (GPI) anchor, strongly induced during infection, was analysed for its biological characteristics and potential role in wheat– Pst interactions. The results showed that PsSOD2 encodes a Cu‐only SOD and responded to ROS treatment. Heterologous complementation assays in Saccharomyces cerevisiae suggest that the SP of PsSOD2 is functional for its secretion. Transient expression in Nicotiana benthamiana leaves revealed that PsSOD2 is localized to the plasma membrane. In addition, knockdown of PsSOD2 by host‐induced gene silencing reduced Pst virulence and resulted in restricted hyphal development and increased ROS accumulation. In contrast, heterologous transient assays of PsSOD2 suppressed flg22‐elicited ROS production. Taken together, our data indicate that PsSOD2, as a virulence factor, was induced and localized to the plasma membrane where it may function to scavenge host‐derived ROS for promoting fungal infection.